Actualization of international and islamic world relations in the face of global peace - Ubaidillah, Akhmad (Islamic perspective on Communication and Psychology, 2024)
Background: The Islamic world plays an important role in maintaining world peace. Islam, as a very rationalist religion, is considered to have the ability to build relationships between communities and makes it possible to build Islamic-based international relations studies. The principles found in the Koran and Hadith form the basis of international relations from an Islamic perspective. However, the international world saw that government leaders changed their political policies towards the Islamic world. On the other hand, this happens when Muslims join a country where the majority of the population is neither Muslim nor secular. Methods: The method used is qualitative and case study analysis through a concept approach to Islamic religious policy as a religion of peace in the context of literature study. Results: The findings obtained in the form of western countries and nations have formed the most real secularization and modernization which has been brought to touch and change almost all aspects of nations and humans throughout the world, including their influence on the Islamic world. In terms of his efforts to find out the origins of these two civilizations and how they were able to relate to each other in a good way, namely give and take, it is possible that a model of the relationship of these two civilizations with the Islamic world can be built. Political selfishness, collateralism, and misinterpretation of human religious teachings, the sources of conflict between the West and the Islamic world are not projections of the future of civilizational or religious differences. Conclusion: In conclusion, all countries, both Western and Muslim, must build dialogue between civilizations in the current context of unstable international development so that they can live together in harmony, peace, and overcome many increasingly serious humanitarian and global problems.